Generalizing Polarity Sensitive Items to Positive Environments in an Artificial Language - Kuhn, Jeremy; Maldonado, Mora (Proceedings of the Amsterdam Colloquium, 2022)
Two well known patterns involve polarity sensitive items. First is Jespersen’s cycle: a polarity sensitive item appearing in the scope of negation is reanalyzed as itself the marker of negation. Second, many NPIs in English have a secondary positive use, with a systematic semantic relation to the polarity sensitive use: in each case, the meaning of the positive form is the logical dual of the NPI. This study investigates these meaning changes using an artificial language learning paradigm, where learners are trained on ambiguous input, and must generalize beyond this input. We ask which generalization strategies appear when learners have to interpret polarity sensitive items in a positive environment.